Accumulation characteristics on a cold, high-alpine firn saddle from a snow-pit study on Colle Gnifetti, Monte Rosa, Swiss Alps - Haeberli, Wilfried; Schotterer, Ulrich; Wagenbach, Dietmar; Haeberli-Schwitter, H.; Bortenschlager, Sigmar (Journal of Glaciology, 1983)
ISSN:0022-1430 ISSN:1727-5652